2024
DOI: 10.1038/s41598-024-53266-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid prototyping of PMMA-based microfluidic spheroid-on-a-chip models using micromilling and vapour-assisted thermal bonding

Monieb A. M. Ahmed,
Klaudia M. Jurczak,
N. Scott Lynn
et al.

Abstract: The application of microfluidic devices as next-generation cell and tissue culture systems has increased impressively in the last decades. With that, a plethora of materials as well as fabrication methods for these devices have emerged. Here, we describe the rapid prototyping of microfluidic devices, using micromilling and vapour-assisted thermal bonding of polymethyl methacrylate (PMMA), to create a spheroid-on-a-chip culture system. Surface roughness of the micromilled structures was assessed using scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…On the other hand, treating micromachined substrates with plasticizers such as cyclohexane, chloroform and acetone can effectively reduce their surface roughness [ 114 , 115 ]. Ahmed et al found that steam treatment with chloroform for 30 s reduced the surface roughness of PMMA-based chips machined by micro-milling and smoothed them to a roughness of about 39 nm [ 116 ].…”
Section: Microfluidic Strategies For the Construction Of Intestinal B...mentioning
confidence: 99%
“…On the other hand, treating micromachined substrates with plasticizers such as cyclohexane, chloroform and acetone can effectively reduce their surface roughness [ 114 , 115 ]. Ahmed et al found that steam treatment with chloroform for 30 s reduced the surface roughness of PMMA-based chips machined by micro-milling and smoothed them to a roughness of about 39 nm [ 116 ].…”
Section: Microfluidic Strategies For the Construction Of Intestinal B...mentioning
confidence: 99%